Dark matter contraction and stellar-mass-to-light ratio gradients in massive early-type galaxies. Issue 1 (10th January 2018) - Oldham, Lindsay J; Auger, Matthew W
Abstract: We present models for the dark and luminous mass structure of 12 strong lensing early-type galaxies. We combine pixel-based modelling of multiband Hubble Space Telescope imaging with Jeans modelling of kinematics obtained from Keck/ESI spectra to disentangle the dark and luminous contributions to the mass. Assuming a generalised NFW (gNFW) profile for the dark matter halo and a spatially constant stellar-mass-to-light ratio ϒ⋆ for the baryonic mass, we infer distributions for ϒ⋆ consistent with initial mass functions (IMFs) that are heavier than the Milky Way's (with a global mean mismatch parameter relative to a Chabrier IMF μα c = 1.80 ± 0.14) and halo inner density slopes that span a large range but are generally cuspier than the dark-matter-only prediction (μ _γ ^′ = 2.01_-0.22^+0.19 ). We investigate possible reasons for overestimating the halo slope, including the neglect of spatially varying stellar-mass-to-light ratios and/or stellar orbital anisotropy, and find that a quarter of the systems prefer radially declining stellar-mass-to-light ratio gradients, but that the overall effect on our inference on the halo slope is small. We suggest a coherent explanation of these results in the context of inside-out galaxy growth, and that the relative importance of different baryonic processes in shaping the dark halo may depend on halo environment.